Detailed Relationship Between the Pattern of Blood Pressure Change During the Valsalva Maneuver and the Degree of Orthostatic Hypotension During the Head-Up Tilt Test in Patients With Orthostatic Intolerance: A Retrospective Case–Control Study. Issue 19 (May 2016) - Kim, Hyun-Ah; Yi, Hyon-Ah; Hong, Jeong-Ho; Lee, Hyung
Abstract : Abstract: Although the head-up tilt (HUT) test and Valsalva maneuver (VM) have been widely used to identify sympathetic adrenergic impairment, the detailed relationship between the degree of orthostatic hypotension (OH) during the HUT test and the pattern of blood pressure (BP) change during the VM remains unknown. This study was performed to investigate the relationship between the degree of OH during the HUT test and the pattern of BP change during the VM. During a 4-year period, a total of 132 consecutive patients with neurogenic OH and 60 healthy controls were enrolled. The degree of OH was defined as mild (associated with a fall in systolic BP [SBP] ≥ 20 < 30 on tilting, n = 49), moderate (associated with a fall in SBP ≥ 30 < 40 on tilting, n = 43), and severe (associated with a fall in SBP ≥ 40 on tilting, n = 40). A standardized battery of autonomic tests, including the HUT test and VM using Finometer devices for recording beat-to-beat BP and heart rate response, and a quantitative sudomotor axon reflex test, was performed. Sympathetic indexes (SIs 1–6) were calculated from the VM. A composite autonomic severity score (CASS) was also obtained to evaluate the severity and distribution of autonomic dysfunction. The degree of OH was compared with the BP decline and recovery during the VM. All indexes exhibited overall significant differences among tested groups ( P  < 0.001). Only SI 3 differentiated all subject groups. Compared with other SIs, SI 3 was best correlated with the amount of decrease in the mean SBP (R 2  = 0.473, P  < 0.001) on tilting. The decrease in mean SBP on tilting was best correlated with CASS adrenergic subscore. SI 3 can differentiate between groups with different degrees of OH. The SI 3 obtained during VM can improve the diagnostic accuracy of autonomic dysfunction in patients with different degree of OH.